Clinical Spectrum, Quality of Life, BRAF Mutation Status and Treatment of Skin Involvement in Adult Langerhans Cell Histiocytosis - Etienne Crickx; Jean-David Bouaziz; Gwenaël Lorillon; Mathilde de Menthon; Florence Cordoliani; Emmanuell Bugnet; Martine Bagot; Michel Rybojad; Samia Mourah; Abdellatif Tazi (Medical Journals Sweden, 2017)
Langerhans cell histiocytosis is a rare histiocytic disorder for which skin involvement and management are poorly described in adults. The aim of this retrospective monocentric study in a national reference centre is to describe the clinical characteristics, quality of life, BRAF mutation status and outcomes of skin involvement in adult patients with Langerhans cell histiocytosis. Twenty-five patients (14 females, mean age 47 years) were included, with a median follow-up of 33 months (range 4-420 months). Patients experienced poor dermatological quality of life despite low body surface involvement. BRAFV600 mutations were detected in 8 of the 18 patients analysed (45%). Eight patients had an associated malignancy. Several treatment options were used and consisted of surgery, topical steroids and carmustine, thalidomide, methotrexate, vinblastine and steroids and cladribine. This study highlights the need to evaluate quality of life and to screen for associated malignancy in adult patients with Langerhans cell histiocytosis.